The plight of menstruating secondary school-girls: a wake-up call for parents and the school system - Metta, Emmy; Mwita, Hellen; Leshabari, Melkizedeck (International Journal Of Community Medicine And Public Health, 2021)
Background: This study assessed secondary schoolgirls’ menstruation experiences and the appropriateness of the school environment in fostering menstrual hygiene management in Tanzania’s rural settings. Methods: A cross-sectional study was conducted among 506 secondary schools girls from Mara Region, Tarime district in Northern Tanzania. Self-administered questionnaire were used for generating data which was analysed using SPSS version 20. Results: The age at menarche for the 506 secondary schoolgirls in the study ranged from 9-17 with a median age of 14 years. Less than a third (31.6%) were informed about menstruation and how to manage it before the first experience. Mothers were the first source of information to 50.2%of the girls. Slightly more than a half (51.4%) were scared and 43.3% were uncomfortable about the experience when it first occurred. More than half (54.8%) missed school for two days and 18% could not go to school for four or more days during menstruation. Almost three-quarters (73.5%) did not have access to sanitary pads. None of the schools had suitable and appropriate WASH facilities to support girls during menstruation. Conclusions: Secondary school girls in Tarime district experience various challenges during their menstruation. Improved awareness and knowledge on menstruation, enhanced access to sanitary and WASH facilities at the school environment would improve menstrual hygiene management among secondary schoolgirls and boost their school attendance and participation in education generally.